Assessing Potential Confounding and Misclassification Bias When Studying the Safety of the Childhood Immunization Schedule - Daley, Matthew F. (Acad Pediatr, 2018)
OBJECTIVES: Some parents are concerned the childhood immunization schedule could increase risk for allergic disorders, including asthma. To inform future safety studies of this speculated association, a parent survey was conducted to examine the risk of misclassification of vaccination status in electronic health record data, and to assess the potential for confounding if asthma risk factors varied by vaccination status. METHODS: A survey was conducted among parents of children 19 to 35 months old at 6 medical organizations within the Vaccine Safety Datalink. Parents of children in 4 vaccination groups were surveyed: 1) no vaccines by 12 months of age and a diagnosis of parental vaccine refusal; 2) consistent vaccine limiting (≤2 vaccines per visit); 3) not consistently vaccine limiting but otherwise undervaccinated with a vaccine refusal diagnosis; and 4) fully vaccinated with no delays and no vaccine refusal. Parents were surveyed about their child’s vaccination status and whether asthma risk factors existed. RESULTS: Among a survey sample of 2043 parents, 1209 responded (59.2%). For receiving no vaccines, the observed agreement between parent report and electronic health record data was 94.0% (κ= 0.79); for receiving all vaccines with no delays, the observed agreement was 87.3% (κ= 0.73). Although most asthma risk factors (allergic rhinitis, eczema, food allergies, family asthma history) reported by parents did not differ significantly between children in the vaccination groups studied, several factors (aeroallergen sensitivity, breastfeeding) differed significantly between groups. CONCLUSIONS: Measurement and control of disease risk factors should be carefully considered in observational studies of the safety of the immunization schedule.